Seasonal change in the abundance of zooplankton and species composition of copepods in the ice-covered sea near Syowa Station, Antarctica - Tanimura, Atsushi; Fukuchi, Mitsuo; Hoshiai, Takao (1986)
P(論文) Seasonal change in abundance and composition of zooplankton was studied in the ice-covered sea near Syowa Station (69°00′S, 39°35′E) over the year from January 1982 to January 1983. Total zooplankton showed two maxima in number in mid-winter and mid-summer, the largest number was recorded in mid-June. Five groups which consisted of copepods, polychaets, eggs, the larvae of benthic animals and appendicularians were the major components. Of which copepods were the most dominant zooplankters, occupying over 80% of the total numbers of the whole samples. A total of 11 species of copepods excluding the harpacticoids were recorded. Among them, Calanus propinquus, Ctenocalanus vanus, Microcalanus pygmaeus, Euchaeta sp., Scolecithricella glacialis, Metridia gerlachei, Oithona frigida, Oithona similis and Oncaea curvata were oceanic components which occurred abundantly in the winter-spring season, while Paralabidocera antarctica and Stephus longipes were characteristic to the Antarctic coastal waters and appeared mainly in the summer season. The larvae and eggs of benthic animals were also coastal and summer constituents. departmental bulletin paper